# math

posted by .

If the sum of the roots of 2 x squared - 6 x + 7 equals zero is multiplied by the product of its roots the result is

• math -

for 2x^2 - 6x + 7 = 0
the sum of the roots = -b/a = 6/2 = 3
product of the roots = c/a = 7/2

so (7/2)(3) = 21/3

## Similar Questions

1. ### Math

Roots Ok, what about roots? Roots of polynomials?
2. ### Algebra

Given the roots, 1/2 and 4, find: (A) The quadratic equation 2x^2-9x+4 ?
3. ### math urgent

Find the result if the sumn of the roots of y= x^2+3x-5 is added to the product of the roots.
4. ### math

the function with the sum of roots of 11 and product of roots is 11 is..?
5. ### Alg 2

By what amount does the sum of the roots exceed the product of the roots of the equation (x-7)(x+3)=0?
6. ### Algebra

The equation x^2+px+q=0, q cannot be equal to 0, has two unequal roots such that the squares of the roots are the same as the two roots. Calculate the product pq. I think the obvious root would be one but the second roots i just can't …
7. ### Math

1. The expression log 5x is equivalent to 2. Write the equation of a polynomial whose sum of the roots equals -3 and the product of the roots equals 9\2?
8. ### math

If the roots of ax^2+bx+c=0 are 6 and 9, then the roots of 3ax^2+3bx+3c=0 are A. 2 and 3 B. 6 and 9 C. 18 and 27 D. -2 and -3 I think since you multiply by 3, the roots are multiplied by 3, but I'm not sure.
9. ### Edge ah am us ,maths

if the sum of the roots and product of the roots of ax^3-6x2+2ax-3b=0 is 3&6 respectively.Then find a and b.
10. ### math

the roots of x^3-3x^2-16c+48=0 , given that the sum of two roots is zero is

More Similar Questions